DIAGNOSIS LABORATORIK FLU BURUNG (H5N1) - B. Mulyadi; Prihatini Prihatini (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2005)
Pandemic of Avian influenzae (AI) cause outbreak in Asia including in Indonesia. Transmission of virus are caused by direct contactwith avian animals, swine poultry, horses or dogs to human, maybe could also happened between human being. Some victims of AIshowed signs and symptoms of repiratoric failure, such as:progresive respiratoric failure difuse, bilateral, infiltration and like ARDS(=acute respiratoric distress syndrome ). Beside those multiorgan failure which showed signs of renal disfunction, including cardiacdilatation and supraventricular tachyarrythmias.Other complications that may happened including ventilator- associated pneumoniae,pulmonary hemorrhage, pneumothorax, pancytopenia, Reye’s syndrome and sepsis syndrome without documented bacteremia.The illnessbegins abruptly acute, worse and manifested with high fever, myalgias, and non-productive cough frequently present in AI (H5N1)infections. This biblography study, consist of reviewing the screening examination such as serologic assay, exactly assay of viral cultureand RT-PCR. The results of this study may get the information which is sensitive and spesific for diagnosing the disease. In this caseshould be known the neccesity of some assays phases to assist the exact diagnosis of AI. AI disease spreading in poultry or migrationendemic area must be monitored.